2018
DOI: 10.1093/mnras/sty2060
|View full text |Cite
|
Sign up to set email alerts
|

Molecular nucleation theory of dust formation in core-collapse supernovae applied to SN 1987A

Abstract: We model dust formation in the core collapse supernova explosion SN 1987A by treating the gas-phase formation of dust grain nuclei as a chemical process. To compute the synthesis of fourteen species of grains we integrate a non-equilibrium network of nucleating and related chemical reactions and follow the growth of the nuclei into grains via accretion and coagulation. The effects of the radioactive 56 Co, 57 Co, 44 Ti, and 22 Na on the thermodynamics and chemistry of the ejecta are taken into account. The gra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
101
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(108 citation statements)
references
References 150 publications
(225 reference statements)
7
101
0
Order By: Relevance
“…They find a grain size distribution with a power law that is steeper than the one inferred by the studies of Wesson et al (2015) and Dwek & Arendt (2015). Moreover, Sluder et al (2016) predict a radically different dust composition compared to the one assumed by most previous studies.…”
Section: Cold Dust In Sn 1987amentioning
confidence: 67%
See 2 more Smart Citations
“…They find a grain size distribution with a power law that is steeper than the one inferred by the studies of Wesson et al (2015) and Dwek & Arendt (2015). Moreover, Sluder et al (2016) predict a radically different dust composition compared to the one assumed by most previous studies.…”
Section: Cold Dust In Sn 1987amentioning
confidence: 67%
“…In the past few years, theoretical computations of dust grain formation have become increasingly more realistic, and go far beyond the classical nucleation theory (e.g., Sarangi & Cherchneff 2015). Sluder et al (2016) presented a detailed analysis of dust formation in SN 1987A based on the so-called molecular nucleation theory, which tracks the abundance of each molecular species with a nonequilibrium chemical reaction network, and which includes effects such as coagulation, grain charging, evaporation, accretion, and chemical weathering. They find a grain size distribution with a power law that is steeper than the one inferred by the studies of Wesson et al (2015) and Dwek & Arendt (2015).…”
Section: Cold Dust In Sn 1987amentioning
confidence: 99%
See 1 more Smart Citation
“…Early dust formation in the Universe (Watson et al 2015;Laporte et al 2017;Hashimoto et al 2018) has been suggested to result from an efficient condensation of dust species in the aftermaths of core-collapse supernovae (CCSNe), requiring each supernova remnant (SNR) to produce a net dust mass ranging between 0.1 and 1 M (Morgan & Edmunds 2003;Dwek et al 2007). Core-collapse nucleation models are able to accommodate high dust condensation efficiencies (e.g., Todini & Ferrara 2001;Nozawa et al 2010;Sarangi & Cherchneff 2015;Sluder et al 2018;Marassi et al 2019), but only during recent years have we been able to observationally confirm the hypothesis of CCSNe being dust facto-E-mail: idelooze@star.ucl.ac.uk ries by detecting the far-infrared (FIR) and sub-millimetre (submm) emission of up to 0.7 M of dust in several Galactic supernova remnants (Barlow et al 2010;Gomez et al 2012;Arendt et al 2014;De Looze et al 2017;Temim et al 2017;Rho et al 2018;Chawner et al 2019) and in SN 1987A (Matsuura et al 2011Indebetouw et al 2014;Matsuura et al 2015), using the Herschel Space Observatory (Pilbratt et al 2010) and the Atacama Large Millimetre Array (ALMA). Recent dust masses inferred for a handful of mostly extragalactic SNRs by probing the effects of dust absorption and scattering on the optical line emission profiles of supernova ejecta, were similarly high (Bevan & Barlow 2016;Bevan et al 2017Bevan et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest for the present work is the formation of carbonaceous dust in the ejecta of corecollapse supernovae, where the formation of dicarbon through radiative association enters chemical models (Liu et al 1992;Cherchneff & Dwek 2009;Clayton & Meyer 2018;Sluder et al 2018) and is an initial step in models of formation of larger carbon clusters through condensation (Clayton et al 1999;Clayton et al 2001;Clayton 2013) or nucleation (Lazzati & Heger 2016). [Later,in Sec.…”
Section: Introductionmentioning
confidence: 99%